GAMBARAN PELAKSANAAN STANDAR PELAYANAN FARMASI KLINIK DI PUSKESMAS KECAMATAN WONOSARI KLATEN - Cahyani, Tiwi Nur; Pambudi, Risma Sakti; Ariastuti, Reni (Jurnal Komunitas Farmasi Nasional, 2023)
The aim of this research is to find out an overview of the implementation of clinical pharmacy service standards at the Wonosari Klaten District Health Center. This research method is a descriptive survey. The collection technique is to use a saturated sample technique. Data analysis in this research is by using the percentage of the results of each parameter. The results of research conducted at the Wonosari Klaten District Health Center regarding clinical pharmacy assessment and prescription services at Wonosari 1 Health Center had a presentation of 100% (very suitable) and Wonosari 2 Health Center at 75% (suitable). Wonosari Community Health Center 1's drug information service has a presentation of 75% (suitable) and Wonosari Community Health Center 2 is 100% (very appropriate). Wonosari 1 Counseling Community Health Center had a presentation of 75% (appropriate) and Wonosari 2 Community Health Center had a presentation of 75% (appropriate). Monitoring of drug side effects at Wonosari Community Health Center 1 had a presentation of 50% (quite appropriate) and Wonosari Community Health Center 2 had 100 (very appropriate). Monitoring of drug therapy at Wonosari Community Health Center 1 had a presentation of 50% (quite appropriate) and Wonosari Community Health Center 2 100% (very appropriate). Evaluation of drug use at Wonosari Community Health Center 1 had a presentation of 75% (appropriate) and Wonosari Community Health Center 2 at 50% (fairly appropriate). So it can be concluded that at Wonosari Community Health Center 1, the percentage is 100%, namely assessment and prescription services, 75% drug information and counseling services, 50% monitoring of drug side effects, monitoring drug therapy and evaluation of drug use, whereas at Wonosari Community Health Center 2, the percentage is 100%. namely drug information services, monitoring drug side effects, monitoring drug therapy and evaluating drug use, 75% assessment and prescription and counseling services